Use of nanoparticles, a modern means of drug delivery, against cryptosporidiosis (Journal of Advanced Veterinary and Animal Research, 2023)
Cryptosporidium is a primary cause of waterborne epidemics, despite being previously considered only an opportunistic pathogen. The disease is associated with significant economic losses in humans and animals that are brought on by diarrhea, which frequently causes dehydration. Contact with diseased people or animals, as well as polluted water, is the major cause of infection. Different drugs are used to control the parasites. Nitazoxanide (NTZ), which is an anti-protozoan and anti-viral drug, can be used to control helminths, viruses, and protozoan parasites as a broad-spectrum antibiotic and has been approved by the food and drug authority (FDA). However, the problem is the development of resistance over a period of time in these parasites. Nanoparticles have received significant attention as possible anti-parasitic agents in recent years. By directing medications to specific cellular locations, targeted drug delivery minimizes the side effects of medications. Nanoparticles have demonstrated effectiveness against different Cryptosporidium species. Nanoparticles loaded with NTZ are found to be an effective remedy for C. parvum in young ones and decrease the oocyst count shed in the stools. Additionally, silver nanoparticles have proven to be effective against C. parvum by releasing silver ions that breach the cell wall of the oocyst, causing the escape of intracellular contents and the destruction of sporozoites within the oocyst. Implementing tiny particles for the purification of consuming water from Cryptosporidium is an economical and environmentally sustainable process. However, the use of nanoparticles in medicine requires more research.J. Adv. Vet. Anim. Res., 10(4): 704–719, December 2023http://doi.org/10.5455/javar.2023.j726